Pelajar Sebagai Agen Perubahan: Menanamkan Wawasan Poilitik dan Sistem Pertahanan Anti Pelanggaran Pemilu di Kelas XII SMA Negeri 14 Oku - Wijaya, Okky Danu; Gusti, Dwi; Mardalena, Ervin; Wiranata, Hilmi (Indo-MathEdu Intellectuals Journal, 2026)
Students are strategic agents of change in fostering political awareness and strengthening democratic defense systems—especially in preventing electoral violations from an early age. This study aimed to embed political insight and understanding of anti-electoral violation defense systems among twelfth-grade students at SMA Negeri 14 OKU, to enhance critical, participatory, and responsible attitudes in democratic life. Using a descriptive qualitative approach, data was collected through socialization activities, interactive discussions, and observation of students’ comprehension and responses. The findings revealed significant improvements in students’ knowledge of core political concepts, types of electoral violations, and their role in safeguarding electoral integrity. Additionally, students demonstrated heightened awareness of the importance of honest and ethical political participation. In conclusion, integrating political awareness and anti-electoral violation defense systems into school environments is critical for shaping a democratic-minded, integrity-driven youth generation capable of elevating the quality of future democracy.